Pravno varstvo manjšin - Klopčič, Vera (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 1993)
Recently, minority issues have again become an important factor of international relations and occupy an important position in discussions on human rights on the whole. The authoress recapitulates the most important regulations of international legal documents adopted recently. She particularly emphasizes those common characteristics which enable the comparison between European standards and internal regulations in Slovenia, which represent a basis for the analysis of questionnaire results within the project "Interethnic relations in the Slovene ethnic territory".
Keywords: mednarodni odnosi; narodne manjšine; pravno varstvo; Slovenija